Tatlin's Dream : Russian Suprematist and Constructivist Art 1910-1923. - Fischer, Wolfgang G.; Milner-Gulland, Robin; Nakov, Andrei Boris (London : Fischer Fine Art Limited, 1973)
Annenkov, Yuri ; Archipenko, Alexander ; Baranoff-Rossiné, Vladimir ; Bogomazov, Alexander ; Burljuk, David ; Ermilov, Vassily ; Exter, Alexandra ; Goncharova, Natalia ; Kliun ; Larionov, Michail ; Lentulov, Aristarkh ; Lissitzky, El ; Malevich, Kasimir ; Matiushin, Mikhail ; Popova, Liubov ; Puni, Ivan ; Rodchenko, Alexander ; Rozanova, Olga ; Tatlin, Vladimir ; Bakst, Leon ; Chagall, Marc ; Csaky, Josef ; Kádár, Bela ; Kandinsky, Wassily ; Moholy-Nagy, Laszlo
biografie
Tatlin's Dream : Russian Suprematist and Constructivist Art 1910-1923, Fischer Fine Art Limited, London, November 1973 - January 1974
Engels
boek
Keywords: Rusland